Marasmius magnus (Marasmiaceae), a new species from the southern Atlantic Forest of Brazil - Magnago, Altielys Casale; Oliveira, Jadson José Souza De; Neves, Maria Alice (Phytotaxa, 2016)
Marasmius magnus, is herein described as a new species from the southern Atlantic Forest, Brazil. It is characterized by the very large basidiomata, small and ellipsoid basidiospores, absence of cheilocystidia and rarely projecting pleurocystidia. The uniqueness of the species is confirmed by ITS data and further supported by a complete morphological description, taxonomic comments, illustrations and photographs.